Correlation between Clinical/Radiographic Features and Inflammatory Cytokine Networks Produced by Macrophages Stimulated with Endodontic Content - Martinho, Frederico Canato [UNESP]; Chiesa, Wanderson M. M.; Leite, Fabio R. M.; Cirelli, Joni Augusto [UNESP]; Gomes, Brenda P. F. A. (Elsevier B.V., 2012)
Introduction: Macrophages are highly activated by endodontic contents. This study investigated the correlation between different clinical signs/symptoms and radiographic features according to the levels of interleukin (IL)-1 beta, tumor necrosis factor alpha (TNF-alpha), IL-6, IL-10, prostaglandin E-2 (PGE(2)), and their networks produced by endodontic content-stimulated macrophages collected from primary endodontic infection with apical periodontitis (PEIAP). Methods: Samples were taken from 21 root canals with PEIAP by using paper points. The presence of exudate (EX), pain on palpation (POP), tenderness to percussion (UP), and the size of the radiographic lesion (SRL) were recorded. Polymerase chain reaction (16S rDNA) was used for bacterial detection and limulus amebocyte lysate (LAL) assay for endotoxin measurement. Raw 264.7 macrophages were stimulated with bacterial contents during 24 hs. The amounts of IL-1 beta, TNF-alpha, IL-6, IL-10 and PGE(2) were measured by enzyme-linked immunosorbent assay. Log-based data were correlated by multiple logistic regression (P < .05). Results: Bacteria and endotoxin were detected in 100% of the samples. IL-6 and TNF-alpha were positively correlated with SRL and EX, respectively (P < .05). Clinical signs/symptoms and radiographic findings were set as dependent variables for EX-positive correlations between PGE(2), IL-1 beta, and TNF-alpha (P < .05), whereas IL-6 and PGE(2) were positively correlated to each other in POP but negatively correlated in SRL (P < .05). When POP and TTP-POP were set as dependent variables, different cytokine networks were found. Conclusions: Our findings suggest different roles for each cytokine in the development of apical periodontitis, whose effects of overlapping networks depend on the signs/symptoms and radiographic features found in endodontic infection. (J Endod 2012;38:740-745)
Keywords: Bacteria; cytokines; endotoxin; macrophages; root canal